The Impact of School Culture, Work Attitude, Stress Management, and Job Satisfaction on Organizational Commitment among Secondary School Teachers - M Ali; Candra Wijaya; Muhammad Dalimunthe; Ikhwanuddin Abdul Majid (JURNAL AL-TANZIM, 2026)
This study aims to analyze the influence of school culture, work attitudes, stress management, and job satisfaction on teachers' organizational commitment in schools. The study used a quantitative, survey-based approach. Data were collected through questionnaires distributed to teachers and analyzed using path analysis to examine relationships among variables and to measure direct and indirect effects. The results indicate that school culture and work attitudes have a direct, positive, and significant effect on teachers' stress management. Furthermore, school culture, work attitudes, and stress management have a direct, positive, and significant effect on teachers' job satisfaction. The coefficient of determination indicates that these four variables together explain 74.8% of the variation in teachers' organizational commitment, while factors outside the research model influence the remaining 25.2%. These findings confirm that teachers' organizational commitment is shaped by the interaction of organizational, work behavior, psychological, and affective factors. The implications of this study suggest that strengthening teachers' organizational commitment can be achieved through developing a supportive school culture, fostering professional work attitudes, and enhancing job satisfaction in an integrated manner, thereby improving teacher performance and the effectiveness of educational organizations.